The AGAPE Process: A Challenge for Transformative Mission and Ecumenism in the 21st Century - Mshana, Rogate R. ca. 21. Jh. (International review of mission, 2008)
This article interprets the links between the AGAPE (Alternative Globalization Addressing People and Earth) process, which the World Council of Churches (WCC) established to seek alternatives to the current process of economic globalization. The scope of this article is limited to the AGAPE process in as far as it contributes to transformative mission and in order to discern an understanding of ecumenism as a sanctuary for the flourishing of life in abundance for all. The article also identifies areas that need further reflection.